PENERAPAN SOCRATIC METHOD DALAM PEMBELAJARAN MATERI SEJARAH ISLAM PADA MASA ERA NEW NORMAL - Hamidatun Nihayah; Zumrotus Sa'diyah; M. Romadlon Habibulloh (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
Teaching and learning is an interaction with the value of education. There is an educational interaction between teachers and students because the teacher delivers learning materials to students in the classroom. The lesson materials that the teacher provides will not provide encouragement (motivation) to students if the delivery in using strategies, methods and techniques is not right. One of the learning methods that aims to enable students to be able to think critically and be good at conversing in a lesson is to apply the Socratic Method, or commonly known as the questioning method. In the context of learning, the Socratic Method is one of the most common and frequently used learning methods in the classroom. Even Socrates viewed that asking questions by teaching was an integral activity. Socr a tic Method is a learning method that is carried out using conversations and debates conducted by two or more people who discuss each other and are faced with several questions.  As for the steps of the Socratic method in learning Islamic history material during the new normal era (1) students prepare questions based on the text that has been read to prepare for discussion; (2) the teacher guides the learner to arrange seating, for example fifteen people sit in a circle in the middle and other learners sit around the inner circle; (3) teachers or learners in the inner circle give divergent questions, for example, what are the things that cause a person to have high cholesterol? What do you do if you find someone throwing garbage into the river?, and (4) learners in the outer circle answer questions by providing data